THE PROPHET MUHAMMAD’S LEADERSHIP - Saeed al-Olaqi, Fahd Mohammed Talib (Journal of Al-Tamaddun, 2014)
The article is a logical and positive argument to William Montgomery Watt’s Muhammad: Prophet and Statesman, which represents to the Western reader imperfect depiction about the Prophet Muhammad’s successful statesmanship as part of his Prophethood. This claim represents a secular ground that the Prophet Muhammad has politically founded Islam. In spite of misunderstanding of Islamic leadership as being religious, Prophet Muhammad cannot be branded as a statesman. It is fairly clear that the Prophet’s leadership is a worldly method which is applicable in real life even without being an Islamic state. The Prophet Muhammad’s techniques in his leadership played a significant part in achieving his goal to deliver the message of Islam to the world. He had all the necessary leadership attributes for success in every aspect of life. Allah the Almighty says, ‘Most certainly, you have in the messenger of Allah an excellent pattern (of behaviour)